Longitudinal Changes in Work Ability, Well-Being, and Psychosocial Risk Factors Among Older Workers: The ProAgeing Study - Fattori, Alice; Barnini, Teresa; Comotti, Anna; Bufano, Pasquale; Laurino, Marco; Russo, Simone; Ferrari, Luca; Ciocan, Catalina; Bonzini, Matteo (La Medicina del Lavoro, 2025)
Background: As the workforce ages, older employees face increasing challenges in adapting to changing job demands, including technological advances and ongoing occupational risks such as shift work and physically demanding tasks. Work ability is a reliable indicator of older workers’ capacity to meet both physical and mental requirements of their jobs. The ProAgeing study, a multicenter investigation specifically focused on workers over 50 years old, examined long-term patterns in work ability, perceived health, and psychosocial risk factors, along with their interactions across this demographic. Methods: Participants completed self-reported questionnaires at baseline and after one year, including the Work Ability Index (WAI), technostress, sleep quality, perceived stress, health, and psychosocial risk factors. A first-difference linear regression model was used to assess predictors of changes in WAI. Subgroup analyses examined differences across occupational roles (bank employees, administrative employees, and manual workers). Results: Of the 470 workers enrolled, 356 (76%) completed the follow-up. A significant decline in average WAI score was observed over 12 months (-1.2 points, p<0.001), mainly in subscales related to work demands and physical illness. Technostress levels slightly decreased, suggesting adaptation over time. Bank employees showed less favorable trends than manual workers, indicating that digitalization and higher job demands significantly affected employees’ well-being, especially older workers. Improvements in perceived health and reduced stress mostly contributed to enhanced work ability. Conclusions: These findings highlight the importance of targeted interventions to enhance health and lower stress among aging workers, supporting their well-being and subsequently their work ability.